1887 Wis. Sess. Laws 684, ch. 161 , § 3, pt. 26 - (:unkn) unknown (General Publisher, 1887)
Authorized the city to regulate and prohibit the concealed carry of any pistol, sling shot, knuckles, bowie knife, dirk, dagger, or any other dangerous or deadly weapon.
--
Keywords: CARRY - CONCEALED